2022
DOI: 10.1088/1741-4326/aca48d
|View full text |Cite
|
Sign up to set email alerts
|

Drift kinetic theory of the NTM magnetic islands in a finite beta general geometry tokamak plasma

Abstract: In [K Imada et al. Nucl. Fusion 59 (2019) 046016] a new 4D drift kinetic nonlinear theory, valid in the limit of a low beta, small inverse aspect ratio, circular cross section, toroidal geometry, to describe the plasma response to the neoclassical tearing mode (NTM) magnetic perturbation is derived. In [A V Dudkovskaia et al. Plasma Phys. Control. Fusion 63 (2021) 054001] this theory is reduced in a low collisionality limit, which allows a dimensionality reduction to a 3D problem to efficiently resolve the col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(36 citation statements)
references
References 31 publications
1
35
0
Order By: Relevance
“…At w ≳ ρ ϑi , the layer around drift islands remains narrow, broadening the layers from both sides of the magnetic island. As was previously noted in [20,21], these separatrix layer effects are expected to be less significant for non-rotating magnetic islands but become crucial when the magnetic island propagation frequency is non-zero (or alternatively in the presence of the equilibrium radial electric field if one works in the magnetic island rest frame). This current version of RDK-NTM is being referred to as RDK-NTM (v.3) in table 1.…”
Section: Dk-ntmmentioning
confidence: 78%
See 4 more Smart Citations
“…At w ≳ ρ ϑi , the layer around drift islands remains narrow, broadening the layers from both sides of the magnetic island. As was previously noted in [20,21], these separatrix layer effects are expected to be less significant for non-rotating magnetic islands but become crucial when the magnetic island propagation frequency is non-zero (or alternatively in the presence of the equilibrium radial electric field if one works in the magnetic island rest frame). This current version of RDK-NTM is being referred to as RDK-NTM (v.3) in table 1.…”
Section: Dk-ntmmentioning
confidence: 78%
“…A prime denotes the derivative with respect to ψ. In [21], it was shown that the second term on the right hand side of equation ( 2) associated with the perpendicular component of the perturbed vector potential, A 1 ⊥ , results in the O δ * ∆ 2 Vt L f 0 corrections in the drift kinetic equation and thus is to be omitted. Here δ * = ρ/L is a small parameter associated with the drift kinetic ordering (ρ is the particle Larmor radius and L characterises the system size) [22], V t is the particle thermal velocity and f 0 is the equilibrium distribution function 6 .…”
Section: Coordinate System and Magnetic Topologymentioning
confidence: 99%
See 3 more Smart Citations